Bilayer Graphene Conductance Analysis based on FET Channel - Vahdat Nazerian; Mohammad Javad Kiani (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2018)
Graphene is considered as a famous nanomaterial because of some parameters such as its large surface–to–volume ratio, high conductivity, high mobility, and strong mechanical and elasticity properties. Therefore, in this work the conductance of two dimensional bilayer graphene (BG) is developed using the Fermi Dirac distribution function. For bilayer graphene two, various stacking structures (AA and AB) have been reported, which have armchair edge. Quantum gradient emerged between the channel and the gate and carrier movement of bilayer graphene is considered as FET channel, which is an important property of FET. Besides, band gap energy and resistance of BG have been modelled in this study. The impact of temperature on the resistance is extensively studied. It is demonstrated that the resistance of BG is the function of temperature and the conductance is increased at higher values of temperature.